2022
DOI: 10.1042/bcj20220016
|View full text |Cite
|
Sign up to set email alerts
|

A central role for amyloid fibrin microclots in long COVID/PASC: origins and therapeutic implications

Abstract: Post-acute sequelae of COVID (PASC), usually referred to as ‘Long COVID’ (a phenotype of COVID-19), is a relatively frequent consequence of SARS-CoV-2 infection, in which symptoms such as breathlessness, fatigue, ‘brain fog’, tissue damage, inflammation, and coagulopathies (dysfunctions of the blood coagulation system) persist long after the initial infection. It bears similarities to other post-viral syndromes, and to myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Many regulatory health bodies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
256
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(266 citation statements)
references
References 275 publications
5
256
0
5
Order By: Relevance
“…However, without fluorescence and with suboptimal equipment these tests were difficult to interpret and thus inconclusive. We want to raise awareness that some (Kell et al, 2022) have hypothesised that microclots could skew blood results to incorrectly come back "normal", for example by entrapment of inflammatory proteins. The slight abnormalities shown as white matter hyperintensities in HAC's MRI scan may be indicative of vascular damage and/or neurodegeneration (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, without fluorescence and with suboptimal equipment these tests were difficult to interpret and thus inconclusive. We want to raise awareness that some (Kell et al, 2022) have hypothesised that microclots could skew blood results to incorrectly come back "normal", for example by entrapment of inflammatory proteins. The slight abnormalities shown as white matter hyperintensities in HAC's MRI scan may be indicative of vascular damage and/or neurodegeneration (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these fibrinaloid microclots are amyloid in nature (as inferred by ThT staining), and as such have been shown to resist degradation via fibrinolytic means (Grobbelaar et al, 2021, Kell and Pretorius, 2017. These amyloid microclots may contribute to poor blood circulation and perfusion, possibly by blocking microcapillaries (Kell et al, 2022), and impairing oxygen and nutrient delivery to various tissues. This provides a ready explanation for the fatigue and other symptoms experienced by individuals with ME/CFS.…”
Section: Discussionmentioning
confidence: 97%
“…When solubilized in the laboratory via a second trypsinization step, it was shown that they contain inflammatory molecules and clotting factors including α(2)antiplasmin (α2AP), various fibrinogen chains, and serum amyloid A (SAA). This pathology may lead to significant endothelial inflammation, (temporary) capillary blockage and hypoxia (Kell et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These micro-clots seem to show resistance to the body’s fibrinolytic processes in patients suffering from post-acute (long) COVID-19. Preliminary results demonstrated the efficacy in reducing the symptoms of long COVID-19 patients through the administration of antiplatelet or anticoagulant therapy [ 77 ].…”
Section: Clinical Manifestation Of Covid-19 and Post-acute (Long) Cov...mentioning
confidence: 99%